The Impact Of Brand Image And Service Quality On Customer Satisfaction At H.E.M.A Resto Kemang Pratama Bekasi - Patricia Febriola Sitorus; Ramang Husin Demolingo (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2026)
Along with rising customer demands, Indonesia's culinary industry continues to grow quickly. These days, customers consider a company's reputation and service quality in addition to the cuisine it serves. In the restaurant business, where competition is getting more intense, customer happiness is heavily influenced by brand image and service quality. The aim of this research is to investigate how customer satisfaction at H.E.M.A. Resto Kemang Pratama, Bekasi, is impacted by brand image and service quality. This study employs an associative strategy in conjunction with a quantitative approach. One hundred respondents who have been or are presently attending H.E.M.A. Resto Kemang Pratama were given questionnaires to complete in order to gather data. Purposive sampling was the method employed. After that, SPSS was used to examine the data in a number of ways, using statistical analyses such as validity, reliability, normality, multicollinearity, heteroscedasticity, multiple regression, t-test, F-test, and coefficient of determination tests determination analysis. It is anticipated that The study is expected to prove that customer satisfaction is positively associated with both brand image and service quality. Additionally, it is anticipated that this research will advance marketing science and service management and serve as a guide for restaurant business players looking to enhance service quality and improve their brand image.